The Impact of COVID-19 on E-Commerce 2020
DOI: 10.51432/978-1-8381524-8-2_5
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults Shopping Online:A Fad or a Trend?

Abstract: Older consumers have been embracing online shopping at an accelerating rate following the COVID-19 outbreak. Higher risks of being infected have forced older adults to adopt new technology and become internet savvy to avoid potentially life-threatening interactions with other customers in brick-and-mortar premises. Industry reports from around the world reveal considerable growth in the number of purchases, frequency of shopping and the amounts spent by this consumer segment. In addition, older consumers have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 36 publications
0
19
0
1
Order By: Relevance
“…With increased time at home and limited options for shopping and socializing, older adults turned to the internet to meet these needs. Studies have found online shopping among older adults did indeed increase during COVID-19 [ 37 , 38 ]. Lastly, it should be noted that the present study found that increased spending was associated with more external support during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…With increased time at home and limited options for shopping and socializing, older adults turned to the internet to meet these needs. Studies have found online shopping among older adults did indeed increase during COVID-19 [ 37 , 38 ]. Lastly, it should be noted that the present study found that increased spending was associated with more external support during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the study found a strong positive relationship between attitude and intention to use VFR technology. This adds to the existing literature on technology acceptance and older adult consumer behavior that integrates the characteristics of older adults to better predict intention to use technology (Kovalenko and Mazaheri, 2021; Wu and Song, 2021). This also encourages other researchers to further expand the existing model by examining antecedents affecting intention to use technology.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, older adults, aged 60 years or older, are becoming a more important segment in developing strategies for v-commerce such as virtual fitting technology, and they have embraced online shopping at an accelerating rate following the COVID-19 outbreak (Kovalenko et al , 2021; World Health Organisation, 2023). Using virtual fitting technology has been particularly beneficial to older adult consumers as they are switching to online shopping as a way of coping with the risks brought on by the pandemic (Xue et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated by news reports from various countries, nonperishable foods have been particularly popular among consumers since the beginning of COVID-19 (Kovalenko & Mazaheri, 2021).…”
Section: Pandemic and Food Demandmentioning
confidence: 99%